Between emotional dependency and loneliness: a cross-sectional study with medical students - Lizbeth Chura; Gilber Chura-Quispe; Cristina Flores-Rosado; Bianca De La Cruz; Nelino Rofner (Millenium, 2025)
Introduction: Emotional dependency and feelings of loneliness have emerged as critical areas of study, reflecting the challenges faced by contemporary society and higher education.